The Bronze Age Site of Tarangul (Aktobe Cis-Urals): Examining One Casting Mo - Darkhan A. Baitileu; Albina Ye. Yerzhanova; Ilaria Calgaro (Oriental Studies)
Introduction. In 2021, the Mugodzhar (Mugalzhar) Crew of the Margulan Institute of Archaeology investigated the site of Tarangul and discovered a casting mold ― a rare artifact of utmost interest related to metal production and processing. Goals. The article seeks to describe and analyze the Bronze Age mold from Tarangul located in the Aktobe Cis-Urals, introduce into scholarly circulation some newly obtained scientific data. Results. The implemented analyses include those of natural science (micro-wear and spectral ones) and comparative typology, the latter to yield a classification of castings and their cultural affiliation. The tool mold has two surfaces with negative impressions. The first one was used to cast three sickles, while the second one (once consisted of two pieces) would cast a flat adze. The shapes attest to the mold was used to cast Kundravinskaya-type sickles widespread across the Late Bronze Age Southern Urals, Middle Volga, and Western Siberia. Kundravinskaya-type sickles are associated with the Alakul culture, the Kozhumberdy cultural group being a local variant of the latter in the region under study. The shape of the impression on the reverse side is characteristic of adzes from the Alakul era discovered in western parts of Eurasia’s steppe zone. The study concludes the mold had first consisted of two pieces and been used to cast adzes, and after the other piece was lost or damaged it started being used to cast sickles. The spectral analysis shows the castings were basically made from copper, and detects some traces of alloying. Another finding is that the three mold negatives were used not simultaneously but rather when and as it was necessary. In general, the conducted tests have well reconstructed the manufacturing techniques and stages of use for the mold from the Late Bronze Age settlement of Tarangul in the Aktobe Cis-Urals, and highlighted certain aspects in the study of molds as a specific source on metal production techniques and technologies in prehistory.